Modulation of Specific Sensory Cortical Areas by Segregated Basal Forebrain Cholinergic Neurons Demonstrated by Neuronal Tracing and Optogenetic Stimulation in Mice - Chaves-Coira, Irene; Barros-Zulaica, Natali; Rodrigo-Angulo, Margarita; Núñez, Ángel (Frontiers in Neural Circuits, 2016)
Neocortical cholinergic activity plays a fundamental role in sensory processing and cognitive functions. Previous results have suggested a refined anatomical and functional topographical organization of basal forebrain (BF) projections that may control cortical sensory processing in a specific manner. We have used retrograde anatomical procedures to demonstrate the existence of specific neuronal groups in the BF involved in the control of specific sensory cortices. Fluoro-gold and Fast Blue fluorescent retrograde tracers were deposited into the primary somatosensory (S1) and primary auditory (A1) cortices in mice. Our results revealed that the BF is a heterogeneous area in which neurons projecting to different cortical areas are segregated into different neuronal groups. Most of the neurons located in the horizontal limb of the diagonal band of Broca (HDB) projected to the S1 cortex, indicating that this area is specialized in the sensory processing of tactile stimuli. However, the nucleus basalis magnocellularis (B) nucleus shows a similar number of cells projecting to the S1 as to the A1 cortices. In addition, we analyzed the cholinergic effects on the S1 and A1 cortical sensory responses by optogenetic stimulation of the BF neurons in urethane-anesthetized transgenic mice. We used transgenic mice expressing the light-activated cation channel, channelrhodopsin-2, tagged with a fluorescent protein (ChR2-YFP) under the control of the choline-acetyl transferase promoter (ChAT). Cortical evoked potentials were induced by whisker deflections or by auditory clicks. According to the anatomical results, optogenetic HDB stimulation induced more extensive facilitation of tactile evoked potentials in S1 than auditory evoked potentials in A1, while optogenetic stimulation of the B nucleus facilitated either tactile or auditory evoked potentials equally. Consequently, our results suggest that cholinergic projections to the cortex are organized into segregated pools of neurons that may modulate specific cortical areas.